Hybrid verrucous squamous cell carcinoma of sinonasal tract: a case report. - Go, J. H. (Korean Academy of Medical Sciences, 1998)
Verrucous carcinoma is a variant of squamous cell carcinoma and should be distinguished from benign papilloma and well-differentiated nonverrucous squamous cell carcinoma. It is rare tumor of the sinonasal tract. Occasionally, conventional squamous cell carcinomatous components may be seen in verrucous carcinoma. This entity is called a hybrid verrucous squamous cell carcinoma. We report a case of hybrid verrucous squamous cell carcinoma occurring in the nasal cavity and paranasal sinus of a 67-year-old male. The removed mass shows the typical feature of verrucous carcinoma, but focally conventional squamous cell carcinomatous area is also noted. The treatment of this case follows verrucous carcinoma, but close follow up is mandatory because it may potentially spread to regional lymph nodes in contrast to pure form of verrucous carcinoma.